2016
DOI: 10.1016/j.slsci.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake has no effect on sleep quality in community dwellers living in a rural Ecuadorian village (The Atahualpa Project)

Abstract: More information is needed to better understand the effect of caffeine on sleep quality at the community level. In a population-based, cross-sectional study design, we aimed to assess the effect of caffeine intake on sleep quality by the use of a multivariate exposure-effect model, adjusted for relevant confounders. All Atahualpa residents aged ≥40 years were identified during a door-to-door survey and interviewed with the Pittsburgh Sleep Quality Index (PSQI) and a structured instrument designed to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
1
4
1
Order By: Relevance
“…Therefore, we assessed the TST, SWS, and REM for five nights during the baseline and the 4‐wk experimental procedure of caffeine intake. These results indicate that daily caffeine consumption at the dose of 60 and 120 mg did not affect sleep quality as measured by PSG recording consistent with recent population‐based study, which showed that caffeine intake has no effect on Pittsburgh Sleep Quality Index score in community‐dwelling adults .…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we assessed the TST, SWS, and REM for five nights during the baseline and the 4‐wk experimental procedure of caffeine intake. These results indicate that daily caffeine consumption at the dose of 60 and 120 mg did not affect sleep quality as measured by PSG recording consistent with recent population‐based study, which showed that caffeine intake has no effect on Pittsburgh Sleep Quality Index score in community‐dwelling adults .…”
Section: Discussionsupporting
confidence: 90%
“…Caffeine’s reputation, of course, means that the substance carries significant expectancy effects, with Sun et al38 finding that an initial dose of caffeine followed by a placebo 4 h later helped extend the cognitive performance of the initial caffeine dose beyond the period when elevated blood pressure and heart rate subsided. However, the Atahualpa Project, using data collected in an Ecuadoran village with no fast food outlets, almost no shift work, and little light or noise pollution during the evening and night hours—and almost certainly a very different cultural orientation toward caffeine—found no impact of caffeine consumption on sleep patterns when controlling for other physiological variables 39. The researchers note that the absence of caffeine impact on night sleep quality may be associated with the absence of other secondary triggers to wakefulness, such as noise or artificial light.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is often ingested by those who are already fatigued, as well as being implicated in causing the fatigue in the first place. Research by del Brutto et al39 noted secondary triggers to wakefulness, such as noise and artificial light, as well as interactions with other factors such as diet which may interfere with sleep.…”
Section: Introductionmentioning
confidence: 99%
“…However, one study found that morning caffeine use affected sleep efficiency and total sleep time negatively [ 107 ]. On the contrary, another study of an Ecuadorian village found no significant effect of daytime caffeine use on nighttime sleep [ 108 ]. Another study found that 400 mg of caffeine - equivalent to four cups of coffee (a high dose considering the average caffeine consumption) - taken 0, 3, or even 6 hours before bedtime significantly disrupted sleep.…”
Section: Reviewmentioning
confidence: 99%